High-Resolution Range and Velocity Measurement Based on Photonic LFM Microwave Signal Generation and Detection - Haixia Cheng; Xihua Zou; Bing Lu; Yao Jiang (IEEE Photonics Journal, 2019)
A microwave photonic approach is proposed to achieve a high resolution enhanced by a factor of 2 for the range and velocity measurement. In the transmitter, a V-shaped linear-frequency-modulated (LFM) microwave signal is generated through the frequency doubling enabled by photonics, with large time-bandwidth product for improving the range resolution, whereas in the receiver, the round-trip duration and Doppler frequency shift (DFS) between the transmitted LFM signal and the received echo signal are mapped into two doubled frequency spacings between two pairs of target sidebands by incorporating two cascaded electrooptic modulators. Thus, the distance and velocity of the moving target can be measured from the beat note of the target sidebands, showing a high resolution improved by a factor of 2. Experiments have been implemented and demonstrated in X-band with a bandwidth of 2 GHz. The distance measurement indicates an absolute error less than 3 mm. In addition, the performance of the proposed system in terms of low power level is discussed.